Information System Analysis of the Process of Opening a Savings Account at Bank "XYZ" Using the Cobit 4.1 Framework - Soleman, Soleman; Mansuri, Mansuri; IP, Remi (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2023)
Effective money storage and easy access system through the bank. The system used at Bank "XYZ" is still experiencing problems in the opening process. When customer service inputs prospective customer data, the input process exceeds the time specified by the system, the process will stop and return to the login display. Based on these problems, an information system audit is needed regarding the maturity level of Bank "XYZ"'s information system. The aim of this research is to determine the maturity level of the process of evaluating and maintaining ICT performance in information systems. This research uses the COBIT 4.1 framework which focuses on the Planning and Organization (PO), Deliver and Support (DS), and Monitor and Evaluate (ME) domains. The research results show that overall based on the maturity level in COBIT, the information system for the process of opening savings at Bank "XYZ" is at level 2 (repeatable but intuitive), which means the company has carried out a repetitive business process but there is no standard procedure for opening savings. To reach level 3 (define process) Bank "XYZ" needs to make process improvements by implementing the COBIT 4.1 Framework, namely PO, ME and DS which have a number of subdomains.